Evaluation of V2X Technologies for the Connectivity of Small Autonomous Vehicles on Secondary Railway Lines - Dereje Mechal Molla; Chadli Hadji; Sassi Maaloul; Leo Mendiboure; Marion Berbineau; Hakim Badis (IEEE Access)
A new concept involving on-demand automatic electric vehicles operating on both road and railway tracks is being developed to rejuvenate secondary railway lines. It is known as FERROMOBILE. Its architecture involves several entities, including vehicles, level crossings, stations, and other infrastructure. The operation of this system necessitates a dynamic, flexible, and safe supervision between these entities, which requires complete and continuous connectivity between them. In this regard, several vehicular communication modes can be created, such as vehicle-to-vehicle (V2V), vehicle-to-infrastructure (V2I) and vehicle-to-network (V2N). Consequently, connectivity can be achieved by utilizing multiple short and long-range wireless technologies, including vehicle-to-everything (V2X). This paper aims to provide a performance analysis of V2X connectivity technologies for autonomous vehicles on secondary railway lines. It first presents an overview of the potential wireless technologies for FERROMOBILE connectivity. Then, we comprehensively describe the developed emulation platform and perform an experimental evaluation of ITS-G5 and C-V2X for V2V/V2I communications, 4G, 5G NR and LoRa for V2N communications. The evaluation was conducted based on V2X channel models consistent with the FERROMOBILE environment. Several evaluations were performed using latency, jitter, packet delivery rate, and packet error rate as key performance indicators. The evaluation results demonstrate that C-V2X outperforms ITS-G5, and 4G/5G NR surpass LoRa’s performance. Indeed, the results show that ITS-G5 and C-V2X can be applicable in V2V/V2I communication and 4G/5G NR in V2N communication for FERROMOBILE architecture.